Editorial: Cancer testis antigens in cancer: Recent developments as cancer biomarkers and therapeutic targets - Adviti Naik (673163) (2022)
Cancer testis antigens (CTAs) form a large family of proteins with highly restricted expression that is limited to male germ cells in the testis and trophoblast cells in the placenta. They are often re-expressed in tumors as a result of differential DNA methylation of their promoter regions, making them highly tumor-specific antigens. Moreover, CTAs are highly immunogenic as the immune system does not recognize them as self-proteins due to the immune privileged environment of the testis. Given their restricted expression patterns and immunogenic nature, CTAs have been identified as attractive candidate targets for anti-cancer therapy. This special issue was designed to highlight new advancements and insights into the oncogenic functions and biomarker or therapeutic potential of CTAs in cancer. CTAs have been implicated in diverse aspects of oncogenesis where individual CTAs have been shown to increase genomic instability, promote tumor growth, invasion and metastasis, impede apoptosis, and enhance angiogenesis (1). Here, Traynor et al. demonstrate that Synovial Sarcoma, X-breakpoint (SSX) proteins are implicated in biological processes that regulate tumor growth as well as metastasis. More specifically, they show that silencing of overall SSX expression reduces tumor growth and completely inhibits metastatic burden of lung and liver in vivo. Molecularly, they found that SSX silencing induces cell cycle stalling, increased apoptosis and reduced migration and invasion potential of melanoma cells. Of note, using the TCGA repository they show that all six protein-coding SSX members are expressed in melanomas with SSX1 and SSX2 being expressed in almost 90% of primary melanomas and metastases, indicating that SSX proteins are attractive therapeutic targets for the majority of melanoma patients. Other Information Published in: Frontiers in Oncology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fonc.2022.1075329